Quality Management and Risk Analysis of Product Defects at Bakers King - Wijaya, Muhammad; Nurrahmani, Syifa (Journal of Collaborative Industrial Management (JCIM), 2025)
This study aims to analyze quality and risk management related to product defects in dry cakes produced by Bakers King. The research was conducted through a three-month survey (February–April 2022), covering a total production of 10,646 units, with 564 defective products identified. The three main types of defects were overflow (54.4%), burnt (23%), and crumbled (22.5%). Analytical methods used in this study included a P-chart for statistical quality control, a fishbone diagram to identify root causes, and Failure Mode and Effect Analysis (FMEA) to evaluate potential risks in the production process. The FMEA results indicated that the highest risks stemmed from inconsistent recipe use (RPN 240) and data recording errors (RPN 224). Proposed mitigation strategies included regular staff training, digitalization of data recording, implementation of standard operating procedures (SOPs), and regular equipment maintenance. Meanwhile, risk transfer strategies were carried out through quality contracts with suppliers and product insurance. This study recommends a comprehensive improvement in quality management systems to reduce product defects and enhance customer satisfaction.